Relationship between communication apprehension and willingness to communicate among TESL undergraduates in a public university in Malaysia - Ismail, Lilliati; Abd Rahman, Fadzilah; Ahmad, Noorlila (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
Teaching English as a Second Language (TESL) undergraduates are trained to become English language educators in the Second Language (L2) context. Thus, they have to be proficient, confident and fluent when speaking in English. However, this is not necessarily true, as they are also L2 speakers who are continuously developing their interlanguage. Also, being proficient does not necessarily mean that one would have low communication anxiety and be highly willing to communicate in a variety of contexts. However, as future English language teachers the TESL undergraduates must be willing to communicate, as their future profession would require them to engage in discussions and present their ideas and knowledge of subject-matter to colleagues, students, educational administrators and parents, among others. Communication apprehension (CA) is one of the factors that could hinder willingness to communicate (WTC), as those who experience high CA would most likely withdraw from communicating or avoid communication. CA is also often compounded by the thought of being evaluated or judged by others. The current research was carried out to find out the relationship between CA and the WTC among the population of TESL students in a public university in Malaysia during meetings, small group discussions, public speaking and interpersonal communication using the Personal Report of Communication Apprehension Scale (PRCA-24) (McCroskey, 1982) and the Willingness to Communicate Questionnaire (McCroskey & Richmond, 1987). There were 145 respondents from the B. Ed TESL programme from year 1 to year 4. The results showed that respondents scored a moderate mean score for CA in all four settings: communicating in groups, inter-personal, public speaking and meetings, and they also scored moderate scores for WTC for all four settings. The highest mean score was recorded for communicating with friends and acquaintances. The respondents also preferred group discussions and public speaking. The lowest mean score was recorded for speaking during meetings. The Pearson correlation coefficient result showed moderate negative correlation between CA and WTC. Results of this study could have pedagogical implications as educators should be aware of the levels of CA and WTC among their learners, and the relationship between CA and WTC to ensure that lessons are geared towards helping to reduce CA and increase WTC among learners to help them become confident and highly motivated individuals who could voice out opinions and ideas in different settings, and communicate content effectively.